#TITLE_ALTERNATIVE# - SINGH (NIM : 13706017); Pembimbing : Dr. Ir. Aditianto Ramelan, MANWEENDERJEET
Low Density Porous Concrete (LDPC) belongs to the class of lightweight concrete, where the pore in the body of material is induced by the addition of expanding agent. Nowadays, LDPC is used in structural application and as insulation. The commercial LDPC is widely known as Autoclaved Aerated Concrete (AAC). With an accurate method of mixing, we could produce LDPC with density less than 1800kg/m3. This research focuses on examining the effect of water-to-cement ratio to the density and thermal conductivity of nan-autoclaved LDPC, which in the analyses is assisted with visual data of the specimen made. Tha sample is made with 20% mass of sand and standardized amount of aluminum paste of 4 grams. The condition of dry sample before hydration is also kept constant with 60% mass of cement and 20% mass of CaO. The variation is mostly on the amount of water added, based on water-to-cement ratio of 0.8, 1, 1.2, and 1.4. The result shows that the condition required of concrete to be an insulation material can be duplicated in the specimen with water/cement ratio of 1,4 in the second set. We could also see aglomeration and pore size variation that are detrimental to the quality of the specimens. Further study is suggested to be undertaken to study thes phenomenon.